2013
DOI: 10.1210/en.2012-1302
|View full text |Cite
|
Sign up to set email alerts
|

Release of Norepinephrine in the Preoptic Area Activates Anteroventral Periventricular Nucleus Neurons and Stimulates the Surge of Luteinizing Hormone

Abstract: The role of norepinephrine (NE) in regulation of LH is still controversial. We investigated the role played by NE in the positive feedback of estradiol and progesterone. Ovarian-steroid control over NE release in the preoptic area (POA) was determined using microdialysis. Compared with ovariectomized (OVX) rats, estradiol-treated OVX (OVX+E) rats displayed lower release of NE in the morning but increased release coincident with the afternoon surge of LH. OVX rats treated with estradiol and progesterone (OVX+EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 65 publications
1
40
0
5
Order By: Relevance
“…Raphael et al also in 2013, reported that the stimulatory effect of NA on the release of gonadotropin-releasing hormone occurs during the positive feedback of ovarian steroids (38). Estrogen up-regulates NA release in the Medio basal hypothalamus.…”
Section: Discussionmentioning
confidence: 98%
“…Raphael et al also in 2013, reported that the stimulatory effect of NA on the release of gonadotropin-releasing hormone occurs during the positive feedback of ovarian steroids (38). Estrogen up-regulates NA release in the Medio basal hypothalamus.…”
Section: Discussionmentioning
confidence: 98%
“…Brainstem noradrenergic innervation of the preoptic area is derived from A1 and A2 cell groups [Fernandez-Galaz et al, 1994]. Disruption of A2 input to the preoptic area is likely to impair the LH surge as preoptic-projecting A2, but not A1 neurons undergo transcriptional activation in response to steroid positive-feedback [Szawka et al, 2013]. The present work documents changes in genomic activity in A2, but not A1 cells after CV4 glucose anti-metabolite administration to steroid-primed OVX female rats, suggesting that hindbrain glucoprivic modifications in NE input to preoptic and other projection sites, after onset of the LH surge, involve adjustments in A2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…NE release into the medial preoptic area is causally related to expression of the LH surge [Honma and Wuttke, 1980; Demling et al, 1985; Mohankumar et al, 1994; Szawka et al, 2013]. Here, an alpha 1 -adrenergic receptor agonist pretreatment strategy was used to determine if diminished receptor activation in this site is germane to hindbrain glucoprivic repression of the GnRH-pituitary LH axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A2 neurons mediate estrogen negative- and positive-feedback regulation of LH secretion, responding to these dualistic signals by release of norepinephrine into the medial preoptic area at basal versus elevated rates [Demling et al, 1985; Mohankumar et al, 1994; Szawka et al, 2013]. Metabolic restraint of the LH surge involves diminished hindbrain NE signaling to the preoptic AVPV, as administration of the alpha-adrenergic receptor agonist methoxamine to that site reverses hindbrain glucoprivic suppression of GnRH neuron Fos immuno-labeling and pituitary LH release [Ibrahim and Briski, 2014].…”
Section: Discussionmentioning
confidence: 99%